Enhancing self-regulated learning among nursing interns: The mediating role of clinical belongingness in academic support systems - Zhu, Ying; Young, Leslie E.; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
Clinical education plays a pivotal role in shaping the professional competence and identity of nursing students. However, the transition from classroom learning to real-world practice presents substantial challenges for nursing interns, particularly in self-regulating their learning processes within emotionally and cognitively demanding environments. This study aimed to investigate the relationship between academic support and self-regulated learning (SRL) among nursing interns and to examine the mediating role of clinical belongingness in this relationship. A cross-sectional survey was conducted among 201 fourth-year nursing interns from a medical university in Jiangsu Province, China. Standardized instruments were used to measure academic support, clinical belongingness, and SRL. Descriptive statistics, Spearman correlation, and structural equation modeling (SEM) were applied to analyze the data. Participants reported high levels of SRL (Mdn = 3.81), slightly high academic support (Mdn = 6.39), and moderate clinical belongingness (Mdn = 3.42). SEM revealed that academic support had both a direct effect (β = 0.235) and an indirect effect (β = 0.086) on SRL through clinical belongingness, which accounted for 26.8% of the total effect. Academic support enhances nursing interns’ SRL both directly and through improved clinical belongingness. These findings underscore the importance of integrating emotional and instructional support systems to promote autonomous, reflective learning during clinical placements.